The etymology, concept and the nature knowability of the sacred numbers in Kazakh and Chinese languages. (Journal of Oriental Studies, 2016)
The main aim of this scientifi c article to introduce the sacred numbers of kazakh and chinese languages. The author reveals the etymology and cognition of numbers.
Keywords: taoist; spiritualism; Mercury; cycle; Confucianism; Buddhism; pentatonic; sky; day; Palace; the Emperor; Beijing; earth; water; wood; fi re and metal